Application of hybrid crow-search with particle swarm optimization algorithm in AGC studies of multi-area systems. (17th February 2020) - Babu, Naladi Ram; Bhagat, Sanjeev Kumar; Saikia, Lalit Chandra; Chiranjeevi, Tirumalasetty
Abstract: This article presents the hybridization of crow-search algorithm with particle swarm optimization (hCA-PSO) in automatic generation control (AGC) studies. A new controller termed by integral-minus-tilt-derivative-control with filter (I-TDN) is proposed and its dynamics are compared with PIDN and TIDN. The proposed controller parameters are optimized by the proposed hCA-PSO technique and are compared with CA, PSO algorithms and are found to be better in terms of settling time, oscillation magnitude. Moreover, the integration of HVDC tie-lines improves system dynamics over AC tie-line. Further, sensitivity analysis suggests that system dynamics with I-TDN controller optimized by hCA- PSO technique obtained at diverse and nominal conditions are robust.